The Development Of Intellectual Humility And Its Relationship With Openness On Experience In Adults And The Elderly - Prof. Dr. Fuad Ali Farhan, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This research aims to identify: Intellectual humility among adults and the elderly according to the two variables: a. Age. B. Sex Openness to experience among adults and the elderly according to the two variables: a. Age b. Gender The significance of the correlation between intellectual humility and openness to experience among adults and the elderly according to the two variables: a. Age b. Sex. The significance of the differences in the correlational relationship between intellectual humility and openness to experience among adults and the elderly according to the two variables: a. Age b. Sex. To achieve the research objectives, the researcher adopted the Krumrei-Mancuso and Rouse (2016) scale, which consists of (21) items distributed into four domains. The researcher also adopted the (Costa & McCrae, 1992) scale, which consists of (28) items distributed into six domains. The two scales were translated into Arabic, verifying the validity of their translation and their psychometric properties of validity and consistency, and after applying it to the research sample of (349) respondents. The data obtained from the sample were statistically processed, and the following results were reached: Adults and the elderly of the ages (18-30) (31-45) (46-59) (60 years and over) possess intellectual humility and openness to experience. The intellectual humility and openness to experience has evolutionary, progressive, not continuous, path through aging. The evolutionary path of the relationship between intellectual humility and openness to experience is not affected by age. The evolutionary pathway of the relationship between intellectual humility and openness to experience with sex is effected for the benefit of males.